2014
DOI: 10.1002/pd.4262
|View full text |Cite
|
Sign up to set email alerts
|

High macrosomia rate in healthy fetuses after enlarged nuchal translucency

Abstract: First trimester PAPP-A MoM and NT MoM are significantly related to birth weight centiles. Enlarged NT is associated with macrosomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
(107 reference statements)
0
3
1
2
Order By: Relevance
“…Hackmon et al's study in 2017 showed a correlation between birth weight and early fetal measurements such as biparietal diameter (BPD) and crown-rump length (CRL), NT measurements, and NT percentiles (11). There is a predominant opinion in the literature that a correlation exists between LGA and NT measurements (2,10,13,27,30,31), but our study revealed no correlation between NT measurements and non-LGA AGA and SGA groups. Therefore, our data show that NT measurements within normal limits can be useful parameters for detecting future macrosomic or LGA fetuses.…”
Section: Discussioncontrasting
confidence: 65%
“…Hackmon et al's study in 2017 showed a correlation between birth weight and early fetal measurements such as biparietal diameter (BPD) and crown-rump length (CRL), NT measurements, and NT percentiles (11). There is a predominant opinion in the literature that a correlation exists between LGA and NT measurements (2,10,13,27,30,31), but our study revealed no correlation between NT measurements and non-LGA AGA and SGA groups. Therefore, our data show that NT measurements within normal limits can be useful parameters for detecting future macrosomic or LGA fetuses.…”
Section: Discussioncontrasting
confidence: 65%
“…[12] Again, similarly, Timmerman et al also identified a positive correlation between NT MoM and birth weight and concluded that the increase in NT was associated with macrosomia. [13] Although Rinat et al reported that NT measurements were correlated with the birth weight of babies in the LGA and SGA in the general population, [14] other researchers reported that there were no such correlations between AGA babies and birth weight. [13] Poon et al reported that not only NT MoM values were effective in predicting macrosomia but also the combination of parameters and maternal characteristics that were used in the screening of aneuploidies were effective in predicting birth weight.…”
Section: Discussionmentioning
confidence: 98%
“…[13] Although Rinat et al reported that NT measurements were correlated with the birth weight of babies in the LGA and SGA in the general population, [14] other researchers reported that there were no such correlations between AGA babies and birth weight. [13] Poon et al reported that not only NT MoM values were effective in predicting macrosomia but also the combination of parameters and maternal characteristics that were used in the screening of aneuploidies were effective in predicting birth weight. [15] In another study conducted by the same author, it was reported that there was a linear relation between decreased NT and SGA.…”
Section: Discussionmentioning
confidence: 98%
“…Sin embargo, en fetos macrosómicos, la TN en el primer trimestre era mayor que en fetos con peso adecuado para la edad gestacional [71][72][73]75,76 .…”
Section: Marcadores Biofísicosunclassified
“…Los modelos de predicción de macrosomía incluyen factores de la historia clínica materna, como edad, peso, talla, raza, antecedente de feto macrosómico, tabaquismo, diabetes mellitus e hipertensión crónica, marcadores biofísicos como la TN y el IP medio de arterias uterinas, y marcadores bioquímicos como la PAPP-A y la b-hCG libre en sangre materna, obteniendo tasas de detección alrededor de un 35 y un 20% para tasas de falsos positivos del 10 y el 5%, respectivamente 33,[71][72][73]76 .…”
Section: Modelos De Predicciónunclassified